Mental Attribution in Interaction: How the Second Person Perspective dissolves the Problem of Other Minds - Gomila Benejam, Antoni; Pérez, Diana (Daimon Revista Internacional de Filosofia, 2018)
In this paper, we will address the question of the impact of the second person perspective of psychological attribution on the traditional problem of knowing other minds. With that purpose in mind, we will introduce the notion of a second-personal perspective of mental attribution within the context of the classical problem of other minds, and discuss the epistemic and ontological implications that follow once the second person perspective is honored. In particular, we will examine how its recognition transforms the traditional problem of other minds, both in its epistemological, ontological and semantical dimensions, and offers a way to go beyond the objective/subjective dichotomy of Modern Philosophy. A proper notion of intersubjectivity, we will argue, is not a simple addition to this dichotomy, but it offers the way to get over the traditional philosophical problems that follow from this modern philosophical paradigm.